Optimizing the Use of QRIS in the Food Stalls: Analysis of Convenience and Risk on Purchasing Decisions - Andy Tri Adriyanto; Novi Tri Utami; Elizabeth Rotua Simamora (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2025)
Abstract. This study investigates the impact of ease of use and perceived risk on QRIS-based purchasing decisions at food stalls in Semarang City, Indonesia. QRIS is a digital payment system. It aims to understand the mediating role of QRIS usage in this relationship. A cross-sectional survey design was employed to collect data from 96 QRIS users. Data analysis included descriptive statistics, correlation analysis tests, and path analysis using SPSS 25 and the Sobel test. Results show that Ease of use significantly influences both QRIS utilization (β = 0.470, p < 0.001) and purchase decisions (β = 0.822, p < 0.001), while perceived risk positively affects QRIS utilization (β = 0.377, p < 0.001) but not directly purchase decisions (p = 0.926). QRIS usage significantly mediates the relationship between ease of use and purchase decisions (Sobel = 5.291, p < 0.001) and between perceived risk and purchase decisions (Sobel = 2.184, p = 0.028). Together, ease of use and perceived risk explain 58.9% of the variance in QRIS usage and 63.5% of purchase decision behavior. Managerially, food stall owners and digital payment providers should prioritize enhancing QRIS usability, improving transaction clarity, and strengthening consumer trust to drive higher purchase conversions and sustain digital payment adoption in micro and small enterprises. Keywords: Ease of use, perceived risk, use of qris, purchase decision, food stalls